Extensional rheology of anode slurries for li-ion batteries containing natural and synthetic graphite - Jun Lee, Won; Park, Nahyun; In Park, Jee; Nam, Jaewook; Hyun Ahn, Kyung; Min Kim, Ju (Journal of Colloid and Interface Science, 2024)
Processing of electrode slurry, which is highly non-Newtonian fluid, is a critical step in the mass production of lithium-ion batteries (LIBs). While extensional flow plays an important role in the electrode slurry processes such as coating, most previous studies have focused only on the shear rheology, due to the lack of a reliable method to measure the extensional rheological properties of the slurry. Here, it is demonstrated that the extensional rheological properties of the anode slurries can be successfully characterized using the stop-flow-dripping-onto-substrate/capillary break-up rheometry (SF-DoS/CaBER). Using this system, it is observed that the extensional rheology of the anode slurry is significantly affected by the blend ratio of the natural and synthetic graphite, as well as the binder and conductive concentrations. Furthermore, the shear rheology-based model predicts much shorter pinch-off times than those measured experimentally, indicating that the yield-stress of the anode slurry is much larger in extensional flow than in shear flow.
Keywords: Anode slurry; Extensional flows; Extensional rheology; Natural and synthetic graphite; Non-Newtonian fluids; Rheological property; Rheometry; Shear rheology; Stop flow; Stop-flow-dripping-onto-substrate/capillary break-up rheometry; Anode slurry; Extensional rheology; Lithium-ion battery; SF-DoS/CaBER